Evaluation of the Quality Characteristics of Premium Pork Loins - L. L. Prill; L. N. Drey; E. A. Rice; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2018)
The objective of this study was to determine shear force, pH, marbling, color characteristics, percentage of intramuscular fat, and purge loss of pork loins from various premium brands in comparison to commodity products. Pork loins (n = 30/brand; Institutional Meat Purchasing Specifications #414) from five premium (PRE A, B, C, D, and E) and two commodity brands (COM A and B) were purchased from food service purveyors and commercial abattoirs. Loins were transported to the Kansas State University Meat Laboratory, Manhattan, KS, and allowed to age 14 to 15 days under refrigerated conditions (36 to 39°F) before fabrication. All PRE brands were similar (P>0.05) with lesser (P<0.05) slice shear force values than COM A, with the exception of PRE C, which had greater (P<0.05) slice shear force values than all other brands evaluated. Similar results were found for Warner-Bratzler shear force, with PRE C having greater (P<0.05) Warner-Bratzler shear force values than all other treatments, and no difference (P>0.05) found among the other PRE products. Commodity A was also tougher (P<0.05) than all PRE brands, except PRE C for Warner-Bratzler shear force. For subjective loin color evaluations, all PRE brands were similar (P>0.05), with only PRE C having a greater (P<0.05) color score than PRE B. Commodity B had a lesser (P<0.05) loin subjective color than all PRE products except PRE B and D. Also, COM B had a greater (P<0.05) L* value (lighter) and lesser (P<0.05) a* value (less red) than all of the other brands. No difference (P>0.05) in a* was found among the PRE brands and only PRE D and E differed (P<0.05) for L*. The two COM products had a similar (P>0.05) chop color score, however COM B was lighter (P<0.05) than all PRE brands. Premium A and E had greater loin visual marbling than all other brands, with no difference (P>0.05) found among the two COM brands and the other 3 PRE brands. However, for chop visual marbling, the two COM brands had less (P<0.05) marbling than all PRE brands, except PRE B and C. For fat percentage, all brands had between 2 to 3% fat, with COM A having less (P<0.05) fat than all PRE brands other than PRE B and D. Little variation was found among brands for pH, but COM B had a lower (P<0.05) pH than all of the other brands. Premium A, C, and D had less (P<0.05) weight lost as purge than any of the other brands. The differences observed within the quality traits evaluated show variation among different premium pork loin brands. This provides evidence that consumers and retailers will receive different levels of pork quality and eating satisfaction dependent upon the premium brand purchased.
Keywords: color; marbling; pork; quality; shear force; tenderness